Conjunctivitis Patients in the Ophthalmology Outpatient Clinic Dr. Soetomo General Academic Hospital, Surabaya, in 2017 - Angeline Hartadhi; Ismi Zuhria; Bambang Hermanto (JUXTA: Jurnal Ilmiah Mahasiswa Kedokteran Universitas Airlangga, 2023)
Highlights:1. Ginger (Zingiber officinale) has antimicrobial activity against UPEC which commonly causes UTI in women.2. The MIC and MBC of ginger against UPEC in this study was 1000 mg/ml. AbstractIntroduction: Conjunctivitis is a self-limiting disease. It can be diagnosed through clinical signs found in the eye examination. The purpose of this study was to define the characteristics of conjunctivitis patients in the ophthalmology outpatient clinic Dr. Soetomo General Academic Hospital, Surabaya, in 2017.Methods: This was a retrospective descriptive observational study of all conjunctivitis patients from the medical history in the ophthalmology outpatient clinic Dr. Soetomo General Academic Hospital, Surabaya, in 2017.Results: There were 497 patients included in this study. Most patients with conjunctivitis were 0-9 years old (19.32%). The most common sign of conjunctivitis was conjunctival hyperemia (80.89%), followed by eye discharge (24.14%), eyelid edema (8.05%), blepharospasm (5.63%), and papillary hypertrophy (5.03%). Most cases of conjunctivitis were bilateral (58.75%). Conclusion: The majority of conjunctivitis was bilateral conjunctivitis. It commonly affects children under ten years old. The most typical finding was conjunctival hyperemia.